myths and labyrinths - Elena Grigoryeva (Проект Байкал, 2018)
In fact, image is mythological. According to Roland Barthes, a myth is like a bottle with the content different from what the label says, like cold coffee in a coke bottle. Another European thinker, Umberto Eco said that the contemporary civilization, our ‘current time’ is built on myths and illusions.